Enhanced cycle life of lead-acid battery using graphene as a sulfation suppression additive in negative active material1. Issue 87 (20th September 2015) - Yeung, Kan Kan; Zhang, Xinfeng; Kwok, Stephen C. T.; Ciucci, Francesco; Yuen, Matthew M. F.
<x xml:space="preserve">Abstract</x> The addition of graphene to negative active materials of lead-acid batteries for sulfation suppression and cycle-life extension is reported. Proposed mechanistic model demonstrates the evolution of PbSO4 surface coverage as cycle number increases.